Microbial contamination during stages of in vitro propagation of Agave angustifolia Haw. - Manuel-Zárate, Fátima; Enríquez-del Valle, José Raymundo; Vásquez-López, Alfonso; Rodríguez-Ortiz, Gerardo; Velasco-Velasco, Vicente Arturo (Revista Mexicana de Ciencias Agrícolas, 2026)
When Agave angustifolia stem tissues are established in vitro, microbial contamination frequently occurs; therefore, the use of antibiotics to solve this problem was evaluated. The purpose of this work was to determine the percentage of stem tissues that had an aseptic establishment and exhibited morphogenetic response in three situations: 1) during in vitro establishment (stage I); 2) in explants in which organogenesis with shoot formation occurred in stage I but were contaminated with bacteria, and these were treated with antibiotics to eliminate contamination; and 3) in aseptic adventitious shoots obtained in stage I and transferred to propagule multiplication medium (stage II). The percentages of aseptic cultures, viable tissues, and organogenic response were evaluated. The results showed that only between 3.68 and 8.73% of stem tissues were aseptic during stage I. However, by applying antibiotics to shoots already formed but contaminated with bacteria at this stage, asepsis was recovered in 52.5% of the cultures. On the other hand, adventitious shoots that were aseptic from stage I and transferred to the multiplication medium (stage II) maintained asepsis at 89.88%; all were viable and showed formation of new shoots. These results indicate that antibiotic treatment in already induced stem tissues is an effective strategy to rescue contaminated cultures, and that transferring aseptic shoots to the multiplication stage allows maintaining aseptic cultures with morphogenetic response.
Keywords: antibiotics; microbial contamination; microorganisms; organogenesis